Sikap Petani Anggota Subak terhadap Program Asuransi Usahatani Padi di Subak Yeh Embang, Desa Yeh Embang Kangin, Kecamatan Mendoyo, Kabupaten Jembrana - KUSUMA, KADEK AGUS NOPTANDIKA; PUTRA, I GEDE SETIAWAN ADI; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018, 2018)
Subak Farmers' Attitudes toward Rice Farming Insurance Program in Subak Yeh Embang, Yeh Embang Kangin Village, Mendoyo Sub-district, Jembrana Regency Food security becomes one of the main goals of national development. One of the efforts undertaken by the Jembrana Regency Government is to implement a special effort (UPSUS) which is the insurance program of paddy farming (AUTP) since 2015. Farmers of Subak Yeh Embang who have not followed the insurance program of rice farming is high (41.46%). The purpose of this research is to investigate the attitude of the farmers of Subak Yeh Embang on paddy farming insurance program. The research was conducted in Subak Yeh Embang, Yeh Embang Kangin Village, Mendoyo Subdistrict, of Jembrana Regency. The respondents were 35 people from the population of 233 farmers who have not followed the paddy farming insurance program determined by using the Proportional Random Sampling method. The findings showed that the attitude of farmers of Subak Yeh Embang can be categorized as agreed with the rice farming insurance by the score of 4.06. The farmers' attitude toward the objectives, targets, benefits, risks, and success of paddy farming insurance program included in the category of strongly agree, while farmers' attitude to compensation, compensation payment, coverage period, amount of claim, and the approval of the insurance claim are included in the category agreed, and the attitude of farmers to the organization of the implementation of rice farming insurance program was the category of doubtful. Based on the result of the research, it is expected that the extension agents and related institutions should be more active in conducting counseling and dissemination of information about rice insurance program (AUTP).